1987
DOI: 10.2307/1942637
|View full text |Cite
|
Sign up to set email alerts
|

A Reevaluation of the ‐3/2 Power Rule of Plant Self‐Thinning

Abstract: Abstract. The self-thinning rule predicts that for a crowded even-aged plant population a log-log plot of average plant mass vs. plant density will reveal a straight "self-thinning" line of slope -%. The rule is supported by examples from many individual populations, and by the existence of an interspecific relationship that yields a line of slope -% in a loglog plot displaying average mass and density data from many populations of different species. I examined and reanalyzed the evidence to evaluate the stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
371
6
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(400 citation statements)
references
References 69 publications
13
371
6
10
Order By: Relevance
“…For α a slightly higher value of -1.75 was chosen because this value is more in line with selfthinning studies that are based on much larger data sets than ours, e.g. (Weller, 1987). The results (Fig.…”
Section: Optimal Closuresupporting
confidence: 64%
See 1 more Smart Citation
“…For α a slightly higher value of -1.75 was chosen because this value is more in line with selfthinning studies that are based on much larger data sets than ours, e.g. (Weller, 1987). The results (Fig.…”
Section: Optimal Closuresupporting
confidence: 64%
“…Although the existence of a universal α (slope of the self-thinning line) has been suggested based on empirical evidence (Reineke, 1933), theory for local competition and probability theory (Dewar and Porte, 2008), empirical studies have shown substantial variability in α, e.g. among species (Weller, 1987). In our analysis we allow α to vary among species.…”
Section: Stand Density and Self Thinningmentioning
confidence: 99%
“…These results offer a different perspective from many studies that have emphasized how competitive and successional processes vary across plant taxa, life forms, and environmental conditions (21,22,(24)(25)(26)(27)(28)(29)(30)(39)(40)(41)(42). They suggest to us that scaling exponents, when measured across orders of magnitude variation in plant size, are relatively independent of phylogenetic affiliation, growth habit, and abiotic environmental features.…”
Section: Discussionmentioning
confidence: 64%
“…For decades, plant scientists have debated the empirical form of the thinning line and the mechanisms that give rise to it (18,(21)(22)(23)(24)(25)(26)(27). Much of the debate has revolved around the value of the exponent, α.…”
mentioning
confidence: 99%
“…While this biomass-density relation has been held as a "law" for decades, recent studies have found little empirical evidence to support its universality and consistency (Weller 1987, Zeide 1987, Lonsdale 1990). In particular, the scaling exponent is not a constant, but rather a variable that is influenced by the shade tolerance of plants under study and taxonomic groups of choice.…”
Section: Biological Allometrymentioning
confidence: 99%